An Ontologically Nihilist Critique of Graham Harman’s Ontological Liberalism - Lovasz Adam (Open Philosophy, 2023)
In Graham Harman’s realist philosophy, which I call “ontological liberalism,” all objects are considered equal, there being no unbridgeable gap between various modes of being. Every object is a unique individual, endowed with a positive being. Any privileging of a certain class of objects over other classes of objects is invalidated. An object is composed of its relations, summarized under the heading of what Harman calls “sensual qualities,” while objects also contain mutually inaccessible essences. Supposedly, every object may be characterized by the duality of relationality and substantiality. According to ontological liberalism, all objects exist. In this essay, I propose an ontological nihilist critique of Harman’s liberal ontology. We cannot exclude the possibility of every object being equally nonexistent. Appearances could pertain all the way down, with no final substance at the end of the infinite chain of appearances. Building on insights gleaned from Jan Westerhoff’s defence of ontological nihilism, I propose a nihilist reconfiguration of Harman’s ontological liberalism. If objects and relations are empty and reality is made of appearances all the way down, no underlying objective essence can or should be posited. Because relations are without basis, lacking in substance, nothing exists, nothing happens, and no objects exist.